Crystallization behavior and thermal stability mechanism of plasma sprayed Al2O3-GAP amorphous ceramic coatings. Issue 12 (September 2022) - Qiang, Linya; Zhang, Xiaozhen; Ai, Yizhaotong; Zhuang, Yin; Sheng, Jing; Zhao, Huayu; Ni, Jinxing; Yang, Kai
Abstract: A novel Al2 O3 -GdAlO3 (GAP) amorphous ceramic coating was in-situ deposited via atmospheric plasma spraying (APS). The crystallization behavior and thermal stability mechanism of Al2 O3 -GAP coating were studied via differential scanning calorimetry (DSC) under isochronal conditions. The nucleation process of Gd4 Al2 O9 (GAM) and α-Al2 O3 phases were more sensitive than the growth process. On the contrary, the nucleation process of GAP phase was duller than the growth process. The activation energy of Al2 O3 -GAP coating was higher than those of almost all amorphous materials reported so far. GAM and α-Al2 O3 phases had a semblable crystallization mechanism: the initial phase evolution was performed by diffusion-controlled growth with a decreasing nucleation rate. As the crystallization fraction increased, the nucleation rate continued to fall. In addition, it was demonstrated that Al2 O3 -GAP coating showed long failure time ( t e 10 % ) of 3.0 × 10 7 min at 1000 K, which was conducive to the application of the coating under high temperature service conditions.